Fast detection of alpha particles in DAM–ADC nuclear track detectors. (February 2015) - Rammah, Y.S.; Ashraf, O.; Abdalla, A.M.; Eisa, M.; Ashry, A.H.; Tsuruta, T.
Abstract: Fast detection of alpha particles in DAM–ADC nuclear track detectors using a new chemical etchant was investigated. 252 Cf and 241 Am sources were used for irradiating samples of DAM–ADC SSNTDs with fission fragments and alpha particles in air at normal temperature and pressure. A series of experimental chemical etching are carried out using new etching solution (8 ml of 10 N NaOH+ 1 ml CH3 OH) at 60 °C to detect alpha particle in short time in DAM–ADC detectors. Suitable analyzing software has been used to analyze experimental data. From fission and alpha track diameters, the value of bulk etching rate is equal to 8.52 μm/h. Both of the sensitivity and etching efficiency were found to vary with the amount of methanol in the etching solution and etching time. The DAM–ADC detectors represent the best efficiency applicable in detectors in the entire range of alpha energies (from 1 to 5 MeV). The activation energies of this etchant have been calculated; track activation energy, E T, has been found to be lower than the bulk activation energy, E B, for the DAM–ADC nuclear track detectors. These results are in more agreement with the previous work. Highlights: Suitable analyzing software has been used. Samples of DAM–ADC detectors have been irradiated with fission fragments. Fast detection method of alpha particles in DAM–ADC detectors. The dependence of etching efficiency upon etchant concentrations.